2021
DOI: 10.31557/apjcp.2021.22.10.3181
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication Through Health Beliefs for Preventing Opisthorchiasis-Linked Cholangiocarcinoma: A Community- Based Intervention in Multicultural Areas of Thailand

Abstract: Objective: This research aimed to study the effects of the risk communication program through the Cambodian folk song to prevent Opisthorchiasis-linked cholangiocarcinoma (OV-CCA). Methods: We conducted the quasi-experimental research between August and December 2017 in the Cambodian communities, one-fourth of ethnic minorities residing in multicultural areas of Sisaket Province, Thailand. The samples consisted of 94 equally people divided into experimental group and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Especially UB, THA were statistically different from other areas for all factors. It is why there have been campaigns in northeast Thailand to deal with OV and CCA for more than 40 years [ 28 – 30 ] until now [ 18 , 19 , 31 , 32 ]. So that people in this area have better knowledge and health beliefs than other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Especially UB, THA were statistically different from other areas for all factors. It is why there have been campaigns in northeast Thailand to deal with OV and CCA for more than 40 years [ 28 – 30 ] until now [ 18 , 19 , 31 , 32 ]. So that people in this area have better knowledge and health beliefs than other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Undesirable behaviors will inevitably affect health. 19 Moreover, Songserm et al 25 studied the effects of the risk communication program through the Cambodian folk song to prevent OV-CCA. The results revealed that the mean scores of health beliefs, social support, and prevention behavior in the experimental group were higher than those of the comparison group with statistical significance.…”
Section: Discussionmentioning
confidence: 99%